Corporate Social Responsibility: A theory of the firm revisited with environmental issues - Domenico Buccella; Luciano Fanti; Luca Gori (Global Labor Organization (GLO), 2024)
The Corporate Social Responsibility (CSR) theory of the firm states that, in strategic markets, social actions lead to a prisoner's dilemma. This paper develops a model with pollution externalities and environmental taxation to incentivise firms' abatement activities through green R&D investments. When the firms' objective function embed environmental issues (Environmental CSR, ECSR), a large spectrum of Nash equilibria emerges, from the Pareto inefficient to the Pareto efficient (ECSR,ECSR), depending on social concern and product differentiation degree. The time (in)consistency policy affects the endogenous market structure of the ECSR decision game more than in the standard CSR without abatement and taxation.
Keywords: H23; L13; M14; Q58; 330; Abatement; Corporate Social Responsibility; Duopoly; Emissions